Pendidikan Kesehatan Tentang Pencegahan Penularan Covid-19 pada Masyarakat di Desa Margaasih Kabupaten Bandung - Lidya Maryani; Linda Hotmaida; Indah Andini; Epi Ratna Putri Mendrofa; Tiara Laksana Putri; Wasty Bella Masneno (PT.Mantaya Idea Batara, 2022)
Covid-19 is a disease with a fairly high level of transmission, so comprehensive efforts to break the chain of transmission of Covid-19 are needed. Health education activities through counseling and the use of various information media will increase public knowledge in preventing the transmission of Covid-19, so as to prevent the disruption of physical and mental health due to Covid-19. The purpose of the activity is to increase the knowledge of the people about preventing the transmission of Covid-19. The method used is counseling through lectures, discussions, questions and answers and demonstrations to the community of RT 01 RW 07 Desa Margaasih Kecamatan Margaasih Kabupaten Bandung. Counseling is carried out in Hybrid (online and offline). The activity stages include the preparation of the required resources, the implementation stage, which is delivering the counseling materials and the evaluation stage by distributing pre and post test questionnaires. The results of the outreach activities showed the achievement of indicators of success. There are 40 peoples from the community joining and actively participated in outreach activities. The results of the distribution of pre and post test questionnaires showed an increase in knowledge in the good category by 55%. From these results it was concluded that health education through counseling could increase public knowledge about preventing the transmission of Covid-19. There is a need for sustainability of community service activities in the form of counseling using more interesting and varied media by expanding the reach of the target participants.